AI-Augmented Penetration Testing: A New Frontier in Ethical Hacking - Thapaliya, Suman; Dhital, Saroj (International Journal of Atharva, 2025)
The accelerating sophistication of cyber threats has outpaced the capabilities of traditional, manual penetration testing approaches. This paper proposes an AI-augmented penetration testing framework that leverages machine learning and reinforcement learning to enhance the efficiency, scalability, and adaptability of ethical hacking efforts. We detail the integration of AI in key phases of the penetration testing lifecycle, including automated reconnaissance via NLP-based parsing of open-source intelligence, vulnerability prediction through supervised learning models trained on historical exploit data, and dynamic attack path generation using reinforcement learning agents. Through empirical evaluation on simulated enterprise environments, our prototype system demonstrates improved detection of deep-seated vulnerabilities and reduction in time-to-compromise metrics compared to conventional methods. We also examine the implications of adversarial machine learning, model drift, and AI explain ability within red team operations, highlighting the need for robust oversight mechanisms. The findings suggest that AI-augmented penetration testing can significantly enhance proactive threat identification and emulate advanced persistent threat (APT) behavior, offering a powerful tool for defenders in a rapidly evolving threat landscape.